O papel de um museu de ciências construído por alunos de ensino fundamental na divulgação científica - Barcellos, Guy Barros (2012)
This written essay presents analysis about data generated by the studend‟s participatory-construction of a Science Museum, inside a private school in Cachoeirinha (RS). The main objective of this study is to understand the participatory-construction‟s contribution to student‟s scientific learning, awakening the naturalistic intelligence. Methodology was mainly qualitative. Seeing the direct implication of the researcher, who was also the teacher, we adopted the recherche-action metodology. The research tools were a diary about the meetings, pictures, interviews and research texts produced by students. The results indicate that Museu da Natureza proved to be a reliable tool to Science learning, once provided moments of scientific endeavour to students. Furthermore, the students posed the importance of this experience to criativity development, since they found themselves challenged to learn researching and also teaching.